Pengaruh Sosialisasi, Pengalaman Kerja dan Latar Belakang Pendidikan Terhadap Pemahaman Usaha Mikro, Kecil dan Menengah dalam Menyusun Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro, Kecil dan Menengah. - Anggraini, Ni Nyoman Elisa; Dewi, Putu Eka Dianita Marvilianti Dewi (Universitas Pendidikan Ganesha, 2024)
This research aims to examine the influence of (1) socialization on understanding in preparing financial reports, (2) work experience on understanding in preparing financial reports, (3) educational background on understanding in preparing financial reports. The research method used is quantitative research. The population in this study consisted of all MSME actors in Buleleng Regency. Sampling was carried out using non-probability sampling with purposive sampling technique. The number of samples used in this research was 94 MSMEs that prepare financial reports in Buleleng Regency. The data used in this research is primary data collected using a questionnaire using a Likert scale. The data analysis used is multiple linear analysis using SPSS 26. The results of this research show that Socialization, Work Experience and Educational Background have a positive and significant effect on understanding in preparing financial reports.